Analysis of The Supreme Court Cassation Decision regarding The Determination of The Status of The Biological Father of Child Out of Wedlock: Case Study Of Decision No. 1055 K/Pdt/2023 - Firda Az Zahra; Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2024)
Humans in their nature are created in pairs by binding themselves to the status of marriage, because with marriage anything that was originally haram will be halal in a legal bond through marriage. Marriage in Article 1 of Law No. 1974 explains that marriage is a physical and mental bond between a man and a woman to form a happy family that is eternal and blessed by Allah SWT. A valid marriage is a marriage that has been recorded at the religious affairs office with all the stipulated provisions. The research method in this study was chosen based on the type of research, problem formulation, and research objectives, and explains the urgency of using this type of research in analyzing research data. The research method in this research is a normative juridical approach which is selected is the research of primary and secondary legal materials. The Civil Code (hereinafter referred to as the Civil Code) refers to children born out of wedlock as Naturlijk Kind (natural children). in article 43 paragraph (1): children born out of wedlock only have a civil relationship with their mother and their mother’s family. In general, this article means that children born as a result of an invalid marriage (out of wedlock), including children resulting from illicit relationships, only have a civil relationship with the mother and her family. The juridical analysis of this decision, the researcher assumes that judges tend to look at Constitutional Court Decision Number 46/PUUVIII/2010 dated February 17, 2012, Article 43 paragraph (1) of Law Number 1 Year 1974 concerning Marriage.